2020
DOI: 10.3390/w12112986
|View full text |Cite
|
Sign up to set email alerts
|

First Captive Breeding Program for the Endangered Pyrenean Sculpin (Cottus hispaniolensis Bacescu-Master, 1964)

Abstract: The strong decline of freshwater fish species in Europe implies that further ex-situ conservation plans should be implemented in the near future. The present study reflects our experience with the Pyrenean sculpin (Cottus hispaniolensis Bacescu-Mester, 1964)—a small cottid endemic to the Hispano-French Garona River basin. In recent years, the Spanish Pyrenean sculpin population has reached a limit situation. Because of that, the non-profit association ADEFFA—with support from the public administration—started … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…The development of lotic-breeding species in captivity has been studied, and it has been found that genetic and environmental factors influence different aspects of larval development (Tanaka & Nishikawa, 2022). In the case of the Pyrenean sculpin, a successful captive breeding program was implemented, and different phases such as nesting behavior, courtship, egg fixation, parental care, hatching, and survival during juvenile development were identified as critical for success (Manubens et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…The development of lotic-breeding species in captivity has been studied, and it has been found that genetic and environmental factors influence different aspects of larval development (Tanaka & Nishikawa, 2022). In the case of the Pyrenean sculpin, a successful captive breeding program was implemented, and different phases such as nesting behavior, courtship, egg fixation, parental care, hatching, and survival during juvenile development were identified as critical for success (Manubens et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…The effective long‐term conservation management of nase and other rheophilic cyprinids should include demographic and genetic monitoring of populations. However, supportive breeding cannot replace in‐situ measures to restore natural reproductive capacity (Manubens et al, 2020). It should only be applied, therefore, in addition to instream and catchment restoration measures (Geist & Hawkins, 2016; Knott et al, 2019), as even small‐scale habitat restoration, such as cleaning spawning gravel, have proved their effectiveness to increase reproductive success in the wild quickly and effectively (Nagel et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…As a result of the strong decline of many freshwater fish and mussel populations, ex‐situ conservation programmes, including captive breeding and restocking, are gaining increasing importance in their conservation (Targońska, Żarski & Kucharczyk, 2008; Roques et al, 2018; Lamothe & Drake, 2019; Lepič, Blecha & Kozák, 2019; Strayer et al, 2019; Manubens et al, 2020; Wetjen et al, 2020; Geist et al, 2021). A successful implementation of supportive breeding measures is particularly crucial if populations are declining very quickly or where species are not able to survive in natural habitats despite extensive in‐situ habitat restoration efforts (Mameri et al, 2018; Manubens et al, 2020). One example is the common nase, Chondrostoma nasus L. (subsequently referred to as nase), a key species of European river systems that was once very widespread.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies are focused on severely imperiled species, such as the Rio Grande Silvery Minnow (Hybognathus amarus (Girard, 1856)), catalogued as Endangered by the IUCN Red List of threatened species; the Spanish toothcarp (Aphanius iberus Valenciennes, 1846), catalogued as Endangered; or the Pyrenean Sculpin (Cottus hispaniolensis Bacescu-Master, 1964), included in the Spanish Catalogue of Threatened Species as Endangered [3,12,13]. Archdeacon et al analyze the inefficiency of a specific conservation tool, the rescue of the Rio Grande Silvery Minnow during streamflow intermittency.…”
mentioning
confidence: 99%
“…They suggest that achieving a better pond ecological status may be necessary to conserve this endangered fish. Manubens et al [12] describe the ex situ conservation plan for the endemic and rare Pyrenean sculpin (Cottus hispaniolensis Bacescu-Mester, 1964). The captive breeding process includes six consecutive phases: nesting behavior, courtship, egg fixation, parental care (incubation), hatching, and survival during juvenile development.…”
mentioning
confidence: 99%